1927 N.J. Laws 180–81, ch. 95, §§ 1–2 - (:unkn) unknown (General Publisher, 1927)
Prohibited a pawnbroker from selling or possessing for sale, loan, or to give away a machine gun, automatic rifle, revolver, pistol, or other firearm, or other instrument of any kind known as a blackjack, slungshot, billy, sandclub, sandbag, bludgeon, metal knuckles, dagger, dirk, dangerous knife, stiletto, bomb or other high explosive. Punishable as a high misdemeanor.
--
Keywords: TRANSFER; MACHINE GUN RESTRICTION